2014
DOI: 10.1080/13562517.2014.880679
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on academic staff involvement in the acquisition and implementation of educational technologies

Abstract: This article presents the results of a study using both quantitative and qualitative data to uncover the extent and nature of the involvement of academic staff in the processes of acquisition and implementation of educational technologies. Actor-network theory (ANT) is used to inform the design of the study and the analysis of the data. Three main areas of investigation are: 1) issues of institutional policy and overall purpose of technology, 2) issues of staff involvement in various activities related to acqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…The relative ineffectiveness of large institutions in facilitating adoption may be further explained by the central-peripheral tension (Clegg, 2003), which depicts the power relationships between the higher education institution and its departments. The literature confirms that academics tend to define their work based on their disciplines (Schneckenberg, 2009) and neglect central institutional policies (Habib & Johannesen, 2014). This suggests centrally-led implementation of learning technologies may be relatively ineffective within disciplines (Hardaker & Singh, 2011).…”
Section: Bureaucracy (N=16)mentioning
confidence: 93%
See 2 more Smart Citations
“…The relative ineffectiveness of large institutions in facilitating adoption may be further explained by the central-peripheral tension (Clegg, 2003), which depicts the power relationships between the higher education institution and its departments. The literature confirms that academics tend to define their work based on their disciplines (Schneckenberg, 2009) and neglect central institutional policies (Habib & Johannesen, 2014). This suggests centrally-led implementation of learning technologies may be relatively ineffective within disciplines (Hardaker & Singh, 2011).…”
Section: Bureaucracy (N=16)mentioning
confidence: 93%
“…The high priority of research and the low priority of teaching make the time and effort required for adoption a threat to research productivity, which may lead to negative responses (D. R. Johnson, 2013). For instance, Habib and Johannesen (2014) found that implemented learning technologies were viewed as authorised administrative procedures: they were rhetorically encouraged but rarely mentioned in performance reviews. The literature further suggests that although rewards and incentives have limited impact on enthusiastic early adopters (Birch & Burnett, 2009), they tend to drive emerging academics towards research and away from teaching (Schneckenberg, 2009).…”
Section: Prioritisation Of Research (N=40)mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite a growing number of studies into technological adoption within teaching and learning in higher education (Habib & Johannesen, ; King & Boyatt, ; Paiva, Morais, Costa, & Pinheiro, ) there is a need for studies that explicitly consider technology and assessment utilisation of academic staff (Bennett et al , ; Deeley, ). Studies which focus on student’s perspectives of technology and assessment prevail including a critical emphasis on the student voice within digital technology use (Manca, Grion, Armellini, & Devecchi, ).…”
Section: Introductionmentioning
confidence: 99%
“…This appeared to be timely, considering growing evidence of the widespread use of a diverse range of technology across the HE landscape, whether this be to engage learners by means of blogging to support learning activities (Duarte, 2015), to capture lessons to enable play back for learners (Ford, Burns, Mitch, & Gomez, 2012), use of mobile devices (Dale & Pymm, 2009) to social media (Nkhoma et al, 2015). Whilst the structures of HE institutions do not automatically lend themselves to the implementation of such educational technologies (Habib & Johannesen, 2014), modern-day learners have been described as 'digital natives' (Prensky, 2001) describing their ability to use and adapt to technology. The links between pedagogy and technology have similarly been noted, and the idea that not only will some forms of technology be useful to meet learner and institutional need but also the idea that Pedagogy will evolve to fit with the capabilities of the new technologies (Burgess & Mayes, 2003, p. 301).…”
Section: Focus Of This Papermentioning
confidence: 99%